The conversion from a Gaussian-like beam to a flat-top beam in the laser hardening processing using a fiber coupled diode laser source. (May 2020) - Zhu, Hongbo; Fu, Xihong; Fan, Shengli; Liang, Lei; Lin, Xingchen; Ning, Yongqiang
Highlights: The beam from diode laser is converted to a flat-top distribution for laser hardening. A detailed investigation on HOSs with different parameters are simulated by using ZEMAX. A Rockwell hardness of 57 HRC and a hardened depth of 1.6 mm are obtained on 35CrMo metal steel. Abstract: In this paper, a laser beam from a fiber coupled diode laser source is converted from a Gaussian-like distribution to a flat-top distribution using a set of homogenization optical system, which makes this diode laser source more favorable for laser hardening. Employing this diode laser source, hardening experiments are performed on 35CrMo metal steel. By optimizing parameters of the hardening processing, at the scanning speed of 1100 mm/min and laser power of 1940 W, a Rockwell hardness of 57 HRC and a hardened depth of 1.6 mm are achieved. Experimental results demonstrate the processing ability of this diode laser source in the industrial laser hardening.